Effect of a lateral square-mesh panel on the catch pattern and catch efficiency in a Mediterranean bottom trawl fishery - BONANOMI, SARA; BRČIĆ, JURE; HERRMANN, BENT; NOTTI, EMILIO; COLOMBELLI, ALESSANDRO; MORO, FABRIZIO; PULCINELLA, JACOPO; SALA, ANTONELLO (Mediterranean Marine Science, 2020)
The current legal codends used in Mediterranean bottom trawl fisheries are at high risk of retaining undersized individuals of several commercial fish species. This entails that codends alone are unable to provide the desired exploitation pattern. A simple technological measure that potentially can provide higher release efficiency of undersized fish are Square-Mesh Panels (SMPs). SMPs are often applied in the upper section of the trawl belly, just ahead the codend. However, recent studies in the Mediterranean have demonstrated that SMPs mounted in this position provided limited release efficiency, because very few fish came into contact with their meshes. In attempt to improve SMPs efficiency in the Mediterranean bottom trawl fisheries, we applied them on the lateral sides of the last tapered section of the trawl belly, just ahead of the codend, and fitted two guiding panels in the trawl belly to enhance fish-SMP contact. We compared the catch performance of a standard commercial trawl with a 52 mm diamond-mesh codend and of a similar trawl fitted with lateral SMPs (70 mm mesh size) in the belly using a twin trawl. The study focused on red mullet (Mullus barbatus), a commercially important species, but data for gurnard (Chelidonichthys lucerna and Chelidonichthys cuculus) were also obtained and analysed. In contrast to previous research on SMPs mounted in the top panel of the trawl, in this study SMPs induced a significant effect on catch performance for red mullet, demonstrating that their lateral position involved greater fish-SMP contact. However, since the test trawl lost a significant amount of legal-sized red mullet compared with the standard trawl, the effect was not wholly positive, possibly due to an excessively large mesh size. Therefore, future studies should be encouraged to test lateral SMPs with smaller mesh sizes.